Molecular mapping of the broad bean wilt virus 2 resistance locus bwvr in Capsicum annuum using BSR-seq - Jung-Min Kim; Joung-Ho Lee; Se-Ran Park; Jin-Kyoung Kwon; Na-Young Ro; Byoung-Cheorl Kang (Theoretical and Applied Genetics, 2024)
Key message Bulked segregant RNA seq of pools of pepper accessions that are susceptible or resistant to Broad bean wilt virus 2 identifies a gene that might confer resistance to this devastating pathogen. Abstract The single-stranded positive-sense RNA virus Broad bean wilt virus 2 (BBWV2) causes substantial damage to pepper ( Capsicum annuum ) cultivation. Here, we describe mapping the BBWV2 resistance locus bwvr using a F 7:8 recombinant inbred line (RIL) population constructed by crossing the BBWV2-resistant pepper accession ‘SNU-C’ with the susceptible pepper accession ‘ECW30R.’ All F 1 plants infected with the BBWV2 strain PAP1 were susceptible to the virus, and the RIL population showed a 1:1 ratio of resistance to susceptibility, indicating that this trait is controlled by a single recessive gene. To map bwvr , we performed bulked segregant RNA-seq (BSR-seq). We sequenced pools of resistant and susceptible lines from the RILs and aligned the reads to the high-quality ‘Dempsey’ reference genome to identify variants between the pools. This analysis identified 519,887 variants and selected the region from 245.9–250.8 Mb of the Dempsey reference genome as the quantitative trait locus region for bwvr . To finely map bwvr , we used newly designed high-resolution melting (HRM) and Kompetitive allele specific PCR (KASP) markers based on variants obtained from the BSR-seq reads and the PepperSNP16K array. Comparative analysis identified 11 SNU-C-specific SNPs within the bwvr locus. Using markers derived from these variants, we mapped the candidate bwvr locus to the region from 246.833–246.949 kb. SNU-C-specific variants clustered near DEM.v1.00035533 within the bwvr locus. DEM.v1.00035533 encodes the nitrate transporter NPF1.2 and contains a SNP within its 5′ untranslated region. The bwvr locus, which contains four genes including DEM.v1.00035533, could represent a valuable resource for global pepper breeding programs.

Establishment of a human induced pluripotent stem cell derived alveolar organoid for toxicity assessment - Jooyeon Lee; Hyosin Baek; Jimin Jang; Jaehyun Park; Sang-Ryul Cha; Seok-Ho Hong; Jieun Kim; Jong-Hee Lee; In-Sun Hong; Seung-Jun Wang; Ji Young Lee; Myung Ha Song; et al. (Toxicology in Vitro, 2023)

Radiological Investigation of Gas Embolism in the East Asian Finless Porpoise (Neophocaena asiaeorientalis sunameri) - Adams Hei Long Yuen; Sang Wha Kim; Sung Bin Lee; Seyoung Lee; Young Ran Lee; Sun Min Kim; Cherry Tsz Ching Poon; Jun Kwon; Won Joon Jung; Sib Sankar Giri; Sang Guen Kim; Jeong Woo Kang; et al. (Frontiers in Marine Science, 2022)
Cetaceans have long been considered biologically adapted to suffer no adverse effects from diving-related tissue gas tension. However, increasing reports of gas embolism in cetaceans inhabiting European, Mediterranean and American waters have challenged the conventional understanding of marine mammal diving physiology. In human hyperbaric medicine, virtopsy techniques such as post-mortem computed tomography (PMCT) facilitate the visualization of gas embolism and could be performed adjunct to conventional autopsy. This research presents the first case of gas embolism identified in an East Asian finless porpoise inhabiting Asian waters. Massive gas embolic lesions were found in the liver, which had been compressing both the lungs and abdominal organs, and signs of pneumonia and parasitic infection were observed in both lungs. It is hypothesized that this porpoise might have been unable to expel in vivo gas bubbles from its circulation due to pulmonary dysfunction. Consequently, gas bubbles agglomerated in the liver, resulting in the development of gas embolic lesions. The findings of the present study provide insights into the occurrence of gas embolism in the East Asian finless porpoise, highlighting the potential of PMCT as a promising tool for the diagnosis of gas embolism in stranded cetaceans.

The chemical constituents of ethanolic extract from Stauntonia hexaphylla leaves and their anti-inflammatory effects - Le Ba Vinh; Se Jin Jo; Phong Nguyen Viet; Dan Gao; Kyoung Won Cho; Eun-Jeong Koh; Sung Sun Park; Young Ran Kim; Young Ho Kim; Seo Young Yang (Natural Product Research, 2021)

CMIT/MIT induce apoptosis and inflammation in alveolar epithelial cells through p38/JNK/ERK1/2 signaling pathway - Jooyeon Lee; Hanbyeol Lee; Soojin Jang; Seok-Ho Hong; Woo Jin Kim; Se Min Ryu; Sung-Min Park; Kyung-Hak Lee; Sung-Joon Cho; Se-Ran Yang (Molecular & Cellular Toxicology, 2019)

l-carnosine induces apoptosis/cell cycle arrest via suppression of NF-κB/STAT1 pathway in HCT116 colorectal cancer cells - Jooyeon Lee; Jeong-Ran Park; Hanbyeol Lee; Soojin Jang; Se-Min Ryu; Hyejin Kim; Donguk Kim; Aera Jang; Se-Ran Yang (In Vitro Cellular & Developmental Biology - Animal, 2018)

Complete mitochondrial genome of the beluga whale Delphinapterus leucas (Cetacea: Monodontidae) - Ji Hyung Kim; Young-Ran Lee; Jeong-Rack Koh; Jin Woo Jun; Sib Sankar Giri; Hyoun Joong Kim; Cheng Chi; Saekil Yun; Sang Geun Kim; Sang Wha Kim; Hye Kwon Kim; Dae Gwin Jeong; et al. (Conservation Genetics Resources, 2017)

Functional characteristics of mesenchymal stem cells derived from the adipose tissue of a patient with achondroplasia - Jeong-Ran Park; Hanbyeol Lee; Chung-Hyo Kim; Seok-Ho Hong; Kwon-Soo Ha; Se-Ran Yang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Isolation of human dermis derived mesenchymal stem cells using explants culture method: expansion and phenotypical characterization - Jeong-Ran Park; Eunjeong Kim; Jungwon Yang; Hanbyeol Lee; Seok-Ho Hong; Heung-Myong Woo; Sung-Min Park; Sunghun Na; Se-Ran Yang (Cell and Tissue Banking, 2015)

Nicotine inhibits the proliferation by upregulation of nitric oxide and increased HDAC1 in mouse neural stem cells - Hanbyeol Lee; Jeong-Ran Park; Jungwon Yang; Eunjeong Kim; Seok-Ho Hong; Heung-Myong Woo; Se-Min Ryu; Sung-Joon Cho; Sung-Min Park; Se-Ran Yang (In Vitro Cellular & Developmental Biology - Animal, 2014)

SPARC is involved in the maintenance of mitotically inactivated mouse embryonic fibroblast cells - Jun Yeon Won; Young Jin Lee; Seung-Joon Lee; Woo Jin Kim; Seon-Sook Han; Se-Ran Yang; Heung-Myong Woo; Sung-Min Park; Hyang-Ah Lee; Seok-Ho Hong (In Vitro Cellular & Developmental Biology - Animal, 2013)

Comparative studies of skeletal muscle proteome and transcriptome profilings between pig breeds - Nam-Kuk Kim; Hye-Ran Park; Hwi-Cheul Lee; Duhak Yoon; Eun-Suk Son; Yeun-Song Kim; Se-Ra Kim; Oun-Hyun Kim; Chang-Soo Lee (Mammalian Genome, 2010)